PENERAPAN MODEL COOCPERATIVE LEARNING TIPE TEAM GAMES TOURNAMENT PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM DI KELAS IV SEKOLAH DASAR - JUBAEDAH JUBAEDAH (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
This research is motivated by the low learning outcomes of students in science learning in class IV Elementary School 1 Cibentar. The purpose of this study is to improve science learning outcomes in fourth-grade elementary school students by using a cooperative learning model of team games tournament type. This research is a classroom action research with two cycles, each cycle is carried out twice the action consists of four stages of activity, namely the planning stage, implementation stage, observation stage, and reflection stage. The subjects of this study were the fourth-grade students of the State Elementary School 1 Cibentar, Jatiwangi District, Majalengka Regency, totaling 17 students. Data collection techniques using observation, learning outcomes tests, and documentation. The research instrument used was an observation sheet on student activities in applying the cooperative learning model of team games tournament type. The results showed that student learning outcomes increased from cycle I to cycle II. In the first cycle, student learning outcomes are 66.66%, and in the second cycle 83.33%. Based on the results of the study, it can be concluded that the application of the cooperative learning model of time games tournament type can improve student learning outcomes in science learning for class IV at SD Negeri 1 Cibentar.